Effective removal of arsenic (V) from aqueous solutions using efficient CuO/TiO2 nanocomposite adsorbent - Farooq, Saima; Siddiqa, Asima; Ashraf, Sobia; Haider, Sabtain; Imran, Saiqa; Shahida, Shabnam; Qaisar, Sara (European Journal of Chemistry, 2022)
The groundwater is one of the biggest natural resources for providing drinking water to millions of people all around the globe. However, the presence of large amount of arsenic(V) in water causes serious health hazards to the consumers which necessitates the development of cost-effective remediation. The CuO/TiO2 nanocomposites were prepared by the precipitation-deposition method for the removal of the arsenate ion (AsO43-) from water. The prepared samples were characterized by powder X-ray diffraction, Fourier transform infrared, and scanning electron microscopy to examine crystallite size and structure, material purity, textural features, morphology, and surface area. The effect of different operating parameters such as pH, contact time, initial concentration of arsenic(V) and nanocomposite dose on the removal rate of arsenic(V) was examined to optimize the adsorption performance of the CuO/TiO2 nanocomposite. In addition, the adsorption mechanism was studied by employing Langmuir and Freundlich adsorption isotherms to gain better understanding of the adsorption mechanism. The Freundlich adsorption isotherm fits well with the experimental data and the maximum adsorption capacity of the Langmuir model was found to be 90 mg/g for arsenic(V). The CuO/TiO2 nanocomposite shows remarkable adsorption performance for the treatment of arsenic(V) contaminated water samples. This study provides a cost-effective solution for the safe use of groundwater contaminated with arsenic.